Placement of Entries, Phono-morphological Information and Emotive Idioms in Al-`Inarah Al-Tahzibiyyah Kamoes Arab-Melajoe - Basuni Imamuddin (Universitas Islam Negeri Sunan Kalijaga, 2019)
In Indonesia there are two kinds of bilingual Arabic-Malay dictionaries and 26 Arabic-Indonesian dictionaries (1925-2018), but all refer to the Dictionary of Al-`Inārah Al-Thżībiyyah Kamoes Arab Melajoe by H. Moehammad Fadloellah and B.Th. Brondgeest (1925). Based on research (Imamuddin, 2017), the placement of entries and subentries is often not consistent. Therefore, there is an urgency to research and revise the dictionary which is the